The formative potential of interdisciplinarity and sociology teaching:: analysis of an experience against Law 13.415/17 (Simbiótica. Revista Eletrônica, 2024)
The article aims to analyse, from an experience of integrated teaching, the training potential of interdisciplinary work in the context of basic education. This involves highlighting the conflict dynamics between the approach that connects the teaching of sociology, philosophy and physical education and the recent High School Reform. We aim to present the components of planning, teaching methodologies and assessment in this pedagogical experience, demonstrating interdisciplinarity as a critical approach to teaching sociology, contrasting with the current orientation of the High School Reform. This study uses a qualitative perspective in which the document analysis technique of Law nº 13.415/2017 is employed. In addition, it incorporates the Experience Report as a research methodology, with the aim of developing academic knowledge from the experiences and practices of students at the Escola de Aplicação da Universidade Federal do Pará.
Keywords: sociology teaching; interdisciplinarity; high school reform